2019
DOI: 10.1002/mus.26432
|View full text |Cite
|
Sign up to set email alerts
|

Adipose‐derived stem cells delay muscle atrophy after peripheral nerve injury in the rodent model

Abstract: Introduction: Injuries to peripheral nerves cause distal muscle atrophy. The effects of adipose‐derived stem cell (ASC) injections into a muscle after injury were examined. Methods: A 1.5 cm defect in the rat sciatic nerve was created, resulting in gastrocnemius muscle atrophy. The nerve defect was repaired with autograft; DiR‐labeled ASCs were injected into the gastrocnemius immediately postoperatively. Quantitation of gross musculature and muscle fiber area, cell survival, fibrosis, lipid deposition, inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 49 publications
1
18
0
2
Order By: Relevance
“…The mechanism of apoptosis is still unclear, and the molecular mechanism controlling the imbalance of protein synthesis and degradation pathways in denervation muscle atrophy remains to be explored. Many studies have explored the inhibition of muscle atrophy: resveratrol has anti-aging effects and can relieve metabolic disorders, and it can signi cantly prevent muscle atrophy after denervation in mice [18]; NF-κB targeted drugs have been used in the treatment of denervation muscular atrophy to delay muscle atrophy, inhibiting apoptosis by inhibiting the classical NF-κB signaling pathway [19]; In the study of Schilling et al, denervated muscular atrophy treated by injection of the allogenic ADSC, showed a decrease in in ammatory factors and achieve delay muscular atrophy [11]. The treatment we have chosen is also intended to delay muscle atrophy by promoting the regeneration of muscle stem cells and acting antiin ammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of apoptosis is still unclear, and the molecular mechanism controlling the imbalance of protein synthesis and degradation pathways in denervation muscle atrophy remains to be explored. Many studies have explored the inhibition of muscle atrophy: resveratrol has anti-aging effects and can relieve metabolic disorders, and it can signi cantly prevent muscle atrophy after denervation in mice [18]; NF-κB targeted drugs have been used in the treatment of denervation muscular atrophy to delay muscle atrophy, inhibiting apoptosis by inhibiting the classical NF-κB signaling pathway [19]; In the study of Schilling et al, denervated muscular atrophy treated by injection of the allogenic ADSC, showed a decrease in in ammatory factors and achieve delay muscular atrophy [11]. The treatment we have chosen is also intended to delay muscle atrophy by promoting the regeneration of muscle stem cells and acting antiin ammation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ADSCs become the rst choice for preclinical studies [7], and they have been widely applied in the eld of cell therapy and tissue engineering regeneration and repair [8][9][10]. Previous studies have shown that transplantation of ADSCs can delay muscular atrophy caused by peripheral nerve injury, suggesting that ADSCs may delay muscular atrophy partly by inhibiting the occurrence of in ammatory responses, but the mechanism remains unclear [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ADSCs become the rst choice for preclinical studies [7], and they have been widely applied in the eld of cell therapy and tissue engineering regeneration and repair [8][9][10]. Previous studies have shown that transplantation of ADSCs can delay muscular atrophy caused by peripheral nerve injury, suggesting that ADSCs may delay muscular atrophy partly by inhibiting the occurrence of in ammatory responses, but the mechanism remains unclear [11].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have confirmed that PNI can be alleviated after ADSC transplantation into nerve injury sites (23,24). A number of studies have previously demonstrated that ADSC transplantation has a regenerative effect on sciatic nerve injury in a rat model (25,26). These studies found that only a small number of ADSCs survived in vivo and that the rate of ADSC differentiation into SC-like cells at the site of injury was low.…”
Section: Introductionmentioning
confidence: 99%